Towards a Unified Functional Trait Framework for Parasites - Llopis-Belenguer, Cristina; Balbuena, Juan Antonio; Lange, Katharina; de Bello, Francesco; Blasco-Costa, Isabel (Trends in parasitology, 2019)
Trait-based research holds high potential to unveil ecological and evolutionary processes. Functional traits are fitness-related characteristics of individuals, which are measured at individual level and defined without using information external to the individual. Despite the usefulness of the functional approach to understand the performance of individuals in ecosystems, and parasitism being the most common life-history strategy on Earth, studies based on functional traits of parasites are still scarce. Since the choice of functional traits is a critical step for any study, we propose a core list of seven functional traits of metazoan parasites, related to three universal challenges faced by organisms (dispersal, establishment, and persistence), and give guidelines to define appropriate functional traits in future parasite community studies.
Keywords: parazitologie; functional diversity; ekosystém; dispersal; zvláštnosti životní historie; community ecology; Parasites; paraziti; Models, Biological; Life Cycle Stages; zvířata; Parasitology; Host-Parasite Interactions; Life History Traits; persistence; functional traits; biologické modely; interakce hostitele a parazita; Ecosystem; stadia vývoje; establishment; Animals